PENINGKATAN AMINOTRANSFERASE SEBAGAI PENANDA CEDERA HATI PADA PENDERITA DEMAM DENGUE - Madina Sahnaz; Corriejati Rita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Dengue infection can give unusual manifestation such as acute liver failure. The increased frequency of this complication in dengueinfection have been reported and have a high mortality. Elevated serum transaminase levels of dengue patients indicate the possibleimpact of dengue virus infection on liver function. The aim of this study was to know the frequency of the increased of aminotransferasein patient with dengue fever. An analysis was made of 67 serologically confirmed dengue cases at Hasan Sadikin Hospital. Thegrade of hepatic aggression was establish according to the alteration in the aminotransferase levels: grade A, have a normal levelsof aminotransferase, grade B have elevated aminotransferase, with increased levels of at least one of the enzymes, grade C elevatedaminotransferase, with the level of at least one of the enzymes increased more than three times the reference value. Among the 67serologically confirmed dengue cases, 7% (n = 5) have a primary dengue infection, 49% (n = 33) have secondary dengue infection,43.3% (n = 29) have a mix infection (secondary and primary infection). 88% (n = 59) have elevated levels of serum aspartataminotransferase (AST) and 68% (n = 46) have elevated level of serum ALT. 67.2% (n = 45) have elevated both AST and ALT. 1.7%(n = 1) presented a normal level of amiotransferase (grade A), 31.3% (n = 21) presented alterations in the aminotransferase (gradeB), 56% (n = 38 ) have elevated aminotransferase more than three times the reference value (grade C). As a conclusion, liver damagewith elevation of aminotransferase was common complication of dengue virus infection.